1984
DOI: 10.1007/bf00276968
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow patterns in painful diabetic neuropathy

Abstract: Summary.Peripheral blood flow is known to be qualitatively increased in diabetic patients with neuropathy. We have measured the actual blood flow in the feet of diabetic patients with neuropathy using non-invasive mercury strain gauge plethysmography and Doppler sonogram techniques and shown that it is increased on average five times above normal at an ambient temperature of 20 ~ -22 ~ Moreover, reduction of this high flow by sympathetic arousal stimuli proved possible in those with severe painful neuropathy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
75
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 20 publications
7
75
0
Order By: Relevance
“…Further evidence to support the assertion that increased blood flow is relevant to the cause of pain is gained from the observation that painful symptoms might improve with maneouvres that reduce blood flow to the limb [16]. In the process of studying blood flow in neuropathy, it was observed that, on inflation of a sphygmomanometer cuff to measure blood flow in the limb, subjects with painful neuropathy often reported that symptoms improved in that limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence to support the assertion that increased blood flow is relevant to the cause of pain is gained from the observation that painful symptoms might improve with maneouvres that reduce blood flow to the limb [16]. In the process of studying blood flow in neuropathy, it was observed that, on inflation of a sphygmomanometer cuff to measure blood flow in the limb, subjects with painful neuropathy often reported that symptoms improved in that limb.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuant nature of painful neuropathic symptoms might suggest a more dynamic underlying cause, such as metabolic or haemodynamic factors, rather than structural lesions. Furthermore, it is recognized that manoeuvres that reduce lower limb blood flow, including vessel occlusion and cooling of the limb, can reduce painful neuropathic symptoms [16]. The aim of this study was to compare sural nerve epineurial haemodynamics in subjects with chronic painful and painless DSP.…”
mentioning
confidence: 99%
“…These studies have demonstrated that both type 1 (insulin dependent) and type 2 (noninsulin dependent) diabetic patients with signs of sensory and/or autonomic neuropathy (e.g., orthostatic hypertension) have increased skin blood flow under basal conditions (2,33) and attenuated reductions in skin blood flow (i.e., vasoconstriction) in response to sympathetic arousal [e.g., produced by mental arithmetic (2) or postural stimuli (29)]. Importantly, deficits in sympathetic vasoconstriction of arterial vessels supplying plantar skin can be demonstrated in both type 1 and type 2 diabetic patients at an early phase of diabetic neuropathy (31,35), perhaps suggesting that sympathetic neurons supplying these vessels are particularly vulnerable to the effects of diabetes.…”
mentioning
confidence: 99%
“…Many years ago, Archer et al (6) showed that diabetic patients with PDN have altered blood flow patterns in the lower limbs. More recently, we found an increase in sural nerve epineurial blood flow in patients with PDN (7).…”
mentioning
confidence: 99%